"Implications of cost-sharing for observation care among Medicare beneficiaries: a pilot survey" - Jennifer N. Goldstein; J. Sanford Schwartz; Patricia McGraw; LeRoi S. Hicks (BMC, 2019)
Abstract Background Medicare beneficiaries hospitalized under observation status have significant cost-sharing responsibilities under Medicare Part B. Prior work has demonstrated an association between increased cost-sharing and health care rationing among low-income Medicare beneficiaries. The objective of this study was to explore the potential impact of observation cost-sharing on future medical decision making of Medicare beneficiaries. Methods Single-center pilot cohort study. A convenience sample of Medicare beneficiaries hospitalized under observation status care was surveyed. Results Out of 144 respondents, low-income beneficiaries were more likely to be concerned about the cost of their observation stay than higher-income respondents (70.7% vs29.3%, p = 0.015). If hospitalized under observation status again, there was a trend among low-income beneficiaries to request completion of their workup outside of the hospital (56.3% vs 43.8%), and to consider leaving against medical advice (AMA) (100% vs 0%), though these trends were not statistically significant (p = 0.30). Conclusion The results of this pilot study suggest that low-income Medicare beneficiaries hospitalized under observation status have greater concerns about their cost-sharing obligations than their higher income peers. Cost-sharing for observation care may have unintended consequences on utilization for low-income beneficiaries. Future studies should examine this potential relationship on a larger scale.